Multi-Stage Design Method for Complex Gas Supply and Exhaust System of Space Station - Dongcai Guo; Qinglin Zhu; Lu Zhang; Jule Zhang; Dong Guo; Fufu Wang; Anping Wang; Ying Xu; Qiang Sheng; Ke Wang (Aerospace)
The supply and exhaust system of the experimental rack on the Chinese space station is a complex integrated system. In this paper, a multi-stage simulation, testing, and verification method is designed for a multi-team, multi-location, and multi-stage integrated gas system. This method is designed to solve the problem of missing input parameters between the gas supply system and the exhaust system. Preliminary tests and strategy verifications were carried out through theoretical simulation and semi-physical simulation, and good calculation results were obtained for the single-rack product. The external systems were tested using a simulation system, and a calculation method was designed to obtain relatively accurate parameters. In the early stage, the performance of the product was predicted using the parameter library of Flomaster and semi-physical simulation methods, but the error was large. In the middle and late stages of development, as some products became realistic, multi-stage testing was carried out using a vacuum simulator, simulated flow resistance, and other methods, achieving a performance prediction with an error of 12% before ground testing. The final ground test and on-orbit test showed that the design and calculation method of this paper is effective. The multi-stage design method proposed in this paper was successfully applied to the integrated gas system of the Chinese space station, which can provide a reference for the design of fluid components in long-term system engineering.